Hybrid Power Sharing: On How to Stabilize the Political Situation in Multi-segmental Societies - Krzysztof Trzciński (Politeja, 2018)
There are various ways of reducing conflicts and of stabilizing the political situation in states where society is made up of many different ethnic groups and religious communities, and where relations between these segments – or between them and the central government – are tense. A particularly important way is the establishment in those states of a political system based on power-sharing (PS), which allows members of various ethnic and religious segments to take part in the exercise of power. The literature on the subject usually discusses two models of PS: consociationalism and centripetalism. A third model is encountered in practice, however, that of hybrid power-sharing (HPS), which combines the institutions of the first two. The main objective of this article is to explain the nature and origins of HPS. As examples, I will use the political systems of Nigeria and Indonesia. In the first part of the article I explain briefly the nature of PS, and of its two main models; in the second I explain what HPS is; in the third I analyze the emergence of HPS, and give the causes of the inclusion of consociational institutions in political systems in which centripetal institutions are dominant, using the cases of Nigeria and Indonesia; I draw conclusions in the final part.